State Plan Proposals 1978-79 Volume I Government of West Bengal - Planning Commission (Planning Commission, 1977)
The Planning Commission have proposed to treat the Fifth Five Year Plan as coming to an end in March, 1978, and to launch a new medium-term plan for the five years 1978-79 to 1982-83 from 1st April, 1978. The annual plan for 1978-79 will, therefore, be the first year of the new medium- term plan.
Government of West Bengal, Development and Planning Department